Brain circulation and spatial mobility of knowledge in Southeast Europe - Mirjana Stankovic; Biljana Angelova; Verica Janeska; Bratislav Stankovic (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
The correlation among agglomeration, externalities, and human capital growth is a question that requires extensive empirical and analytical investigation. This article hypothesizes that entities that cluster in geographic space take advantage of external economies and develop more rapidly than do isolated entities. In geography of innovation stickiness, knowledge spillovers are major drivers of technological progress and economic growth. This in turn, might incentivize intellectual mobilization of the Southeast European countries' highly skilled Diaspora by creating opportunities for emergence of a brain circulation network. Over the past twenty years, the number of researchers and scientists in the countries of Southeast Europe (SEE) has seriously decreased. Many highly educated Southeast Europeans leave their countries in search of a better life. They are attracted to career opportunities, higher salaries, and better overall conditions abroad. This paper gives an overview of the main theories underpinning spatial mobility of knowledge, brain drain and brain circulation in developing countries. It also provides an analytical snapshot of the brain drain trends in the SEE, focusing on Macedonia, the brain drain leader in the region. In the end, it proposes public policy mechanisms for intellectual mobilization of the SEE highly educated Diaspora by envisioning the creation of a brain circulation network that will foster a regular set of interactions, collaborations, joint grant proposals, joint research projects, co-authorships, visitor exchange, joint ventures and alike, between the highly educated Diaspora and their counterparts in the countries of origin. This will provide expatriates with the opportunity to transfer their expertise and skills to the country of origin, without necessarily returning home permanently. In this way, the SEE countries will have access to the knowledge and expertise of the expatriates, and to the knowledge networks that they form in the host countries.
Keywords: 650; agglomeration economies; human capital; brain circulation; brain drain; brain gain; Diaspora; innovation policy; economic growth; science policy; technology transfer